Neuroprotective properties of Sanguinoderma rugosum extracts against glutamate-induced hippocampal cells / Sam Si Enn - Sam , Si Enn (2022)
Oxidative stress and neuroinflammation are two intertwined pathologic factors in a wide range of neurological diseases. With heightening prevalence of neurological diseases due to rising life expectancy around the globe, searching for novel and alternative therapeutic candidates is urgently needed. Sanguinoderma rugosum (synonym: Amauroderma rugosum) has been traditionally used as a natural remedy to reduce inflammation, prevent unceasing crying, cancer and epileptic fits in China and Malaysia. However, the potential neuroprotective and neurorescue effects of S. rugosum against glutamate-induced neurotoxicity remain largely unexplored. In the present study, extracts from S. rugosum were evaluated for their neuroprotective and neurorescue properties using in vitro HT-22 mouse hippocampal neuronal cells. The mycelia of S. rugosum were cultivated in submerged liquid culture and freeze-dried prior to solvent extraction. MTT cell viability assay was performed to determine the neurotoxicity, neuroprotective and neurorescue activities of S. rugosum extracts at 24 and 48 h. Flow cytometric analysis was conducted to investigate the effects of S. rugosum extracts on the intracellular reactive oxygen species (ROS) production and cell death induced by glutamate. The constituents present in SR-HF fraction were identified through GC/MS analysis. The preliminary findings showed that all extracts did not exhibit cytotoxic effect on HT-22 cells. Upon 24 h incubation, pre-treatment with both SR-EE (12.5 μg/mL) and SR-HF (100 μg/mL) markedly (P<0.05) restored the loss of cell viability to 65.80 ± 1.85% and 89.76 ± 9.50%, respectively. The glutamate-induced ROS generation was effectively declined by SR-EE and SR-HF to 13.8% and 8.0%, respectively. The population of late apoptotic/early necrotic cells showed reduction after pre-treatment with SR-HF, with value of 13.3%. However, an increase in the percentage of late apoptotic/early necrotic cells were shown in the glutamate-induced cells after pre-treatment with SR-EE, with value of 26.6%. In general, all extracts demonstrated neurorescue effect against glutamate-induced cells at 24 and 48 h. Eleven compounds were identified in SR-HF by GC/MS analysis, of which the linoleic acid, ergosterol and ethyl linoleate are the major chemical compounds. In short, these results demonstrated that SR-HF may be considered as a potent therapeutic agent to be used in treating neurological disorders related to oxidative stress and neuroinflammation.